2022
DOI: 10.1007/s13353-022-00683-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance, phylogenetic typing, and virulence genes profile analysis of uropathogenic Escherichia coli isolated from patients in southern Iraq

Abstract: Of the most common infectious diseases that occur mainly by uropathogenic Escherichia coli (UPEC) is urinary tract infections (UTIs). The purpose of this study was to investigate virulence factors, antibiotic resistance, and phylogenetic groups among UPEC strains isolated from patients with UTI in southern Iraq. A total of 100 UPEC isolates were collected from urine samples of UTI patients from various hospitals in southern Iraq, and con rmed by morphological and biochemical tests. Antimicrobial susceptibility… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
2
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
(31 reference statements)
5
2
1
1
Order By: Relevance
“…In addition, a worrisome finding from this study is a relatively high resistance rate for nitrofurantoin (14.81%) in isolates of E. coli . This is similar to a previous study demonstrating that E. coli isolates were resistant to nitrofurantoin (21%), 45 but in contrary to a few previous studies with a low prevalence of nitrofurantoin resistance in E. coli isolates. 46 , 47 The potential explanation of these resistance to antibiotics could be attributed to the inappropriate and excessive use of these antibiotics in the empirical treatment for E. coli- related infections in different parts of the world.…”
Section: Resultssupporting
confidence: 90%
“…In addition, a worrisome finding from this study is a relatively high resistance rate for nitrofurantoin (14.81%) in isolates of E. coli . This is similar to a previous study demonstrating that E. coli isolates were resistant to nitrofurantoin (21%), 45 but in contrary to a few previous studies with a low prevalence of nitrofurantoin resistance in E. coli isolates. 46 , 47 The potential explanation of these resistance to antibiotics could be attributed to the inappropriate and excessive use of these antibiotics in the empirical treatment for E. coli- related infections in different parts of the world.…”
Section: Resultssupporting
confidence: 90%
“…In our study, phylogenetic group B2 had the highest prevalence among the UPEC strains with strains belonging to group A being the second most prevalent among the strains. These results are consistent with other studies in Iran ( 32 ) and Iraq ( 15 ). Commensal strains may become virulent by random functional point mutations adaptive for pathogenic environments and a genomic deletion that enhances pathogenicity.…”
Section: Discussionsupporting
confidence: 94%
“…The highest sensitivity of the strains was found against amikacin, meropenem, and imipenem which is consistent with other findings in Ethiopia ( 14 ), Iraq ( 15 ), and Turkey ( 12 , 18 ). In contrast, high resistance was found against erythromycin, ticarcillin, ampicillin, and piperacillin, a finding which is commonly reported for UPEC strains in Iraq ( 15 , 19 ), Romania ( 4 ), Turkey ( 12 ), Thailand ( 20 ), and India ( 21 ) and it could be partly due to the common use of these antibiotics for treatment of UTI in these countries. The high level of ESBL-positive UPEC in our study is of great concern and we found similar results in less developed countries ( 22 24 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…по отношению к фосфомицину устойчивость для этих групп была высокой и низкой соответственно. рядом исследователей отмечены аналогичные результаты по превалирующей частоте встречаемости резистентности к абп у представителей упэк филогенетической группы B2 [5,18], а также подгруппы B2 3 [19].…”
unclassified